Online Learning PBL Model with the STS Approach to Improve High School Students’ Critical Thinking Ability - Gita Lorencia S.; Budi Jatmiko (PendIPA Journal of Science Education, 2021)
The research aims to describe the effectiveness of online learning PBL ( Problem Based Learning)model with STS (Science Technology Society) approach to improve students’ critical thinking ability. Research is Pre experimental with pre-test and post-test design conducted at Labschool UNESA High School in the academic year 2020/2021. The research sample consisted of 56 students of eleventh grade Natural Science. Collecting data is done through pre-test, applying the model PBL with the STS approach through the Google meet, and the last is post-test. Analysis data using paired t-test, analysis of n-gain, and independent t-test. According to analysis data, students' critical thinking ability scores are suffering an increase that is significant at ? = 5% with an average n-gain in the medium category and consistent in both classes. The conclusion is that the online learning PBL model with the STS approach effectively improves the critical thinking ability of high school students.